Influence recreacion loads on ekosistem condition of the Ile-Alatau national park (the Northern Tien Shan) (Eurasian Journal of Ecology, 2016)
As a result of surveys in the Ile-Alatau National Park identified the negative effects of immoderate recreational pressure, causing degradation of plant communities and ecosystems of the Northern Tien Shan.
Keywords: recreation; ecosystem; flora; Ile-Alatau National Park; Northern Tien-Shan